Pemahaman Hadits “Makan dengan Tiga Jari” dan “Perbedaan Usus Orang Mukmin dan Orang Kafir Ketika Makan” (Kajian Ma’anil Hadits) - Muhammad Fatih (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2017)
The understanding about hadith should consider many aspects, such as customs or traditions of the environment in which the hadith was narrated, the situations and conditions at that time, form of the expression used, the classification between the means in which local-temporal and individualistic objectives, paying attention to the hadiths that have same theme, making sure the meaning of words of the hadith, and another important aspect is the presence of the Prophet in various positions and functions, in which the Prophet's role as a human being, as a person, as a husband, as a messenger of God, as the statesman, as society leaders, as war leader and as a judge. Therefore, it is very important to understand of the hadith in its accordance; when it is understood textually, contextually, universally, based on the situation and locality, since rigid, radical, and static understanding means reject the existence of Islam as shalih li kulli zaman wa makan.